What’s Love Got to Do with It? A Longitudinal Study of the Culture of Companionate Love and Employee and Client Outcomes in a Long-term Care Setting - Barsade, Sigal G.; O’Neill, Olivia A. (Administrative Science Quarterly, 2014)
In this longitudinal study, we build a theory of a culture of companionate love—feelings of affection, compassion, caring, and tenderness for others—at work, examining the culture’s influence on outcomes for employees and the clients they serve in a long-term care setting. Using measures derived from outside observers, employees, family members, and cultural artifacts, we find that an emotional culture of companionate love at work positively relates to employees’ satisfaction and teamwork and negatively relates to their absenteeism and emotional exhaustion. Employees’ trait positive affectivity (trait PA)—one’s tendency to have a pleasant emotional engagement with one’s environment—moderates the influence of the culture of companionate love, amplifying its positive influence for employees higher in trait PA. We also find a positive association between a culture of companionate love and clients’ outcomes, specifically, better patient mood, quality of life, satisfaction, and fewer trips to the emergency room. The study finds some association between a culture of love and families’ satisfaction with the long-term care facility. We discuss the implications of a culture of companionate love for both cognitive and emotional theories of organizational culture. We also consider the relevance of a culture of companionate love in other industries and explore its managerial implications for the healthcare industry and beyond.